The high degree of similarity in histopathological and clinical characteristics between radiogenic and sporadic papillary thyroid microcarcinomas in young patients - Bogdanova, Tetiana; Chernyshov, Serhii; Zurnadzhy, Liudmyla; Rogounovitch, Tatiana I.; Mitsutake, Norisato; Tronko, Mykola; Ito, Masahiro; Bolgov, Michael; Masiuk, Sergii; Yamashita, Shunichi; Saenko, Vladimir A. (Frontiers in Endocrinology, 2022)
The potential overtreatment of patients with papillary thyroid microcarcinoma (MPTC) has been an important clinical problem in endocrine oncology over the past decade. At the same time, current clinical guidelines tend to consider prior radiation exposure as a contraindication to less extensive surgery, even for low-risk thyroid carcinomas, which primarily include microcarcinomas. This study aims to determine whether there are differences in the behavior of MPTC of two etiological forms (radiogenic and sporadic), including invasive properties, clinical data, and recurrence in patients aged up to 30 years. For this purpose, 136 radiogenic (from patients aged up to 18 years at the time of the Chornobyl accident) and 83 sporadic (from patients born after the Chornobyl accident) MPTCs were selected and compared using univariate and multivariate statistical methods in a whole group and in age and tumor size subgroups. No evidence of more aggressive clinical and histopathological behavior of radiogenic MPTCs as compared to sporadic tumors for basic structural, invasive characteristics, treatment options, and postoperative follow-up results was found. Moreover, radiogenic MPTCs were characterized by the lower frequencies of oncocytic changes (OR = 0.392, p = 0.004), nodal disease (OR = 0.509, p = 0.050), and more frequent complete remission (excellent response) after radioiodine therapy (OR = 9.174, p = 0.008). These results strongly suggest that internal irradiation does not affect tumor phenotype, does not associate with more pronounced invasive properties, and does not worsen prognosis in pediatric or young adult patients with MPTC, implying that radiation history may be not a pivotal factor for determining treatment strategy in such patients.